Analysis and design of base-isolated suspension bridge under seismic loads - Kyaw , Lin Htat (2008)
Suspension bridges have been firmly established as the most efficient and cost effective structural form in the 500-ft to 1500-ft span range. Today, the suspension bridge is most suitable type for very long-span bridge and actually represents 20 or more of all the longest span bridges in the world. Behavior of suspension bridge is great importance as the influence of moving loads, seismic and wind forces on these structures. Seismic isolation introduces to avoid resonance with the typical predominant frequencies of earthquakes, in order to reduce the shear forces, deflections, and floor accelerations of a building, and, consequently, prevent damage of its structural and non-structural elements. In this study damper is used as isolation and energy dissipation devices for bridge subjected to earthquake loads. The simplified model is three-span continuous and main span has 260-ft and each side span has 120-ft with a steel bridge deck. Main cables are parallel-wire strands and pylons are Portal type. The bridge is designed for equivalent traffic loads of HS 20-44 trucks specified by American Association of State Highway and Transportation Officials (AASHTO). A realistic analytical suspension bridge model is developed by using STAAD.Pro finite element program. The response spectrum analysis method is used from UBC 1997 code. This paper discusses the effect of base-isolator on design of suspension bridge. Then, compared the analysis results in different between normal support condition and spring support condition. From the comparison results, the axial force in main cable is reduced by 22.6 %. Axial forces in girder are reduced about 40 % in all members of girder under spring support condition.